326 Comparison of Genomic Relationship Matrices Using Differing Number of SNP in Pooled DNA Analyses. (7th December 2018) - Boldt, R; Keele, J; Kuehn, L; McDaneld, T; Smith, T; Enns, R
Abstract: Pooled DNA analyses reduce the cost of genome wide association experiments designed to identify novel-trait markers. Genotype frequencies for the pools are derived using the proportion of florescence for each locus versus a genotype call. It has been shown that a reduced number of SNP can be used that produce equivalent GBLUP outcomes using genotype calls. However, the ability to use reduced numbers of SNP for a genomic relationship matrix (G) has not been examined when using the pooled DNA. The objective was to characterize the equivalence of alternative G, based on pooled DNA with differing numbers of SNP. The data consisted of 106 pools with approximately 96 animals each. Pools were formed using treatment status of feedlot cattle that showed clinical signs of Bovine Respiratory Disease. All pools were genotyped using a high density Bovine genotyping array. Data filtering removed all SNP that had an average minor allele frequency of less than 0.01 across all pools. This resulted in 776, 830 SNP available for forming a full genomic relationship matrix (GF ). Randomly sampled SNP ranging from 100 to 770, 000 increased by 500 SNP were used to form the reduced G matrices (GR ) with 10 replications for each level. To test equivalence of matrices GR was standardized using Eigen value decomposition of GF . If the matrices are proportional, the variation in the Eigen values of the standardized matrix would be near 0. A scree plot was made using average Eigen value variation over the replications of SNP levels. The scree plot shows an inflection point at 1, 100 SNP and the addition of more SNP past this point quickly approaches 0 variation in the Eigen values for the standardized matrix. The results showed a reduced number of SNP can be used, and the relationships of the pools should be proportional to GF .